Construction and Operation of a dispersive Laser Raman Spectrograph using interference filter (Journal of Bangladesh Academy of Sciences, 2009)
A dispersive laser Raman system was designed and constructed using a helium-neon (He-Ne) laser as an excitation source, and an interference filter in the reflection mode for Raleigh filtering instead of the more common holographic notch filter. A commercially available spectrograph equipped with a cooled CCD camera was used to acquire the Raman spectra. The constructed laser Raman spectrograph was found to have excellent performance and sensitivity. Stokes Raman spectra of some common chemicals were acquired by the system, and the wavelengths of spectral lines agreed well with the literature values, within experimental error. The useful spectral range of the system is about 200-4000 cm-1. It was also possible to acquire anti-Stokes Raman spectra of one chemical (CCl4) without much difficulty. We hope to use the system for chemical identification of molecules as well as quantitative chemical analysis. To our knowledge, this is the first laser Raman system constructed in Bangladesh. doi: 10.3329/jbas.v32i1.2451 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 121-129, 2008